Lactate dehydrogenase activity during tooth movement under 1.0 N and 1.5 N continuous force applications - Shahrul Hisham Zainal Ariffin,; Nurfathiha Abu Kasim,; Rohaya Megat Abdul Wahab,; Abdul Aziz Jemain, (Universiti Kebangsaan Malaysia, 2013)
The aim of this study was to observe the pattern of lactate dehydrogenase (LDH) activity in GCF and the rate of tooth movement at two different orthodontic forces (1.0 N and 1.5 N). Twelve subjects participated in this study and was chosen based on the inclusion criteria. Each subject received forces of 1.0 N and 1.5 N for tooth movement either on the left or right side of the maxillary canine. GCF sample was collected at mesial and distal sites of the canines before applying the appliance (week 0) and every week for 5 weeks after tooth movement (week 1 to week 5) where baseline activity served as control. LDH activity was assayed spectrophotometically at 340 nm. The tooth movements were measured from casted study models. LDH specific activity at mesial sites in 1.0 N and 1.5 N force groups, respectively increased significantly (p<0.05) only on week four and throughout the treatment when compared with baseline. At distal sites, LDH specific activity with 1.5 N was higher than 1.0 N throughout the five weeks of tooth movement. LDH specific activity with 1.5 N force increased at both mesial (week 2) and distal sites (week 3) with significant different (p<0.05) when compared with 1.0 N force. Tooth movement with 1.5 N showed significantly faster (p<0.05) at the end of week 5 when compared with 1.0 N. LDH has the potential as a biological marker of inflammation during tooth movement.A force of 1 N was more suitable to be used although less tooth movement was produced because less inflammation caused by the force can be useful in orthodontic treatment for patients with stabilised periodontal diseases compared with 1.5 N force.